2021
DOI: 10.1200/jco.20.01370
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Transplant-Ineligible Patients With Newly Diagnosed Multiple Myeloma: Findings From the Phase III MAIA Trial

Abstract: PURPOSE To evaluate the effects of daratumumab, lenalidomide, and dexamethasone (D-Rd) versus lenalidomide and dexamethasone (Rd) on patient-reported outcomes (PROs) in the phase III MAIA study. PATIENTS AND METHODS PROs were assessed on the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30-item and the EuroQol 5-dimensional descriptive system at baseline and every 3 months during treatment. By mixed-effects model, changes from baseline are presented as least squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…Other research in TNE NDMM patients found that overall HRQoL recovers after 6 to 12 months of therapy management. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other research in TNE NDMM patients found that overall HRQoL recovers after 6 to 12 months of therapy management. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…Other research in TNE NDMM patients found that overall HRQoL recovers after 6 to 12 months of therapy management. 30,31 As reliance of patients on caregivers increased during the first year after diagnosis, caregiver burden also rose with a peak three months after diagnosis. Those caring for TNE NDMM patients reported greater burden and time dedicated to caring compared to TE individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This modification significantly enhances CAR T-cell-based immunotherapy by enriching the product's population of memory-like T-cells to enhance T-cell durability and potency. 220 The drug was the subject of two recent reports of an ongoing dose-escalation study (NCT03274219) of 44 the presence of memory-associated T-cell markers and peak expansion and duration of response, providing some tentative support for the mechanistic hypothesis underlying the product's design. 221,222 Johnson and Johnson's contribution to this arena is ciltacabtagene autoleucel (JNJ-68284528; JNJ-4528; LCAR-B38M; cilta-cel), which differs from other BCMA-targeted T-cell therapies by being directed against two BCMA epitopes (VH1 and VH2), a feature which improves affinity for BCMA-expressing cells.…”
Section: Chimeric Antigen Receptor (Car) T-cellsmentioning
confidence: 99%
“…74 In a quality-of-life analysis of patients enrolled in the MAIA study, 49 49.1% of patients treated with lenalidomide/dexamethasone and 57.3% of patients treated with daratumumab/lenalidomide/ dexamethasone experienced worsening of self-reported cognitive functioning at any point while receiving treatment, though the duration, persistence, and functional impact of these changes are not reported. 75 There is much work to be done to examine cognition in older adults with myeloma longitudinally and identify those at greater risk for cognitive decline.…”
Section: Tightrope Of Treatment: Avoiding Undertreatment and Overtreatment In Older Adultsmentioning
confidence: 99%